Pendidikan Karakter dan Dakwah Dalam Kisah Luqman Al-Hakim Perpektif Tafsir Tematik - Zamroni Wafa (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
The narrative of Luqman al-Hakim in the Al-Quran provides numerous wise insights. It includes monotheism, the myth of a noble parent, and rules and processes for relating to family and the larger community. The goal of this study is to comprehend the character values included in Al-Qur'an Luqman's letter and how they might be applied to pupils. The research method employed is qualitative, using library research. Content analysis techniques are used in data analysis. Inductive qualitative data analysis is characterized by the development of a relationship pattern or a hypothesis based on the data acquired. Documentation from the Qur'an, as-Sunnah, books, otoritative books, journals, and encyclopedias served as the study's instruments. The finding shows that the values ​​of character education contained in Surah Luqman verses 12-19 cover three aspects, namely aqidah education, sharia education, and moral education.